Wilson Disease in a Turkish Population: Molecular Insights into an Old Disease with Reported and Novel Variants - Abdullatif Bakır; Vehap Topçu; Büşranur Çavdarlı (Gazi Medical Journal)
Objective: Wilson’s disease (WD) is a rare autosomal recessive genetic liver disorder with hepatic, neurological, or psychiatric manifestations between 1st to 5th decades. WD is caused by homozygous or compound heterozygous pathogenic variants in the ATP7B gene. In this study, we aimed to contribute to the ATP7B gene variant spectrum in a Turkish population of WD patients. Methods: We investigated 49 patients from 46 families to determine the underlying molecular etiology of WD. DNA samples were extracted from peripheral blood. The molecular genetic diagnosis was performed using the next-generation sequencing method. Results: Molecular genetic analysis revealed 26 different variants, two of which were novel c.1707+4A>G (IVS4+4A>G) and p.M497K in 34 patients from 31 different families. p.M769Hfs*26 was the variant with the highest allele frequency at 11.3%, followed by the p.H1069Q variant (8%). The classification of the variants according to the molecular mechanism was as follows: missense 61.5%, splice site and frameshift 15.4%, and non-sense 0.08%. Conclusion: In this study, we aimed to contribute the variant spectrum of the ATP7B gene in the Turkish population and the genetic profile of WD with the obtained data.